Die Wolke, Tschernobyl und die Folgen - Jurschick, Karin (Germany, 2011)
2011, 25th anniversary of Chernobyl. The world commemorated the first global industrial disaster. After decades of research, billions of investments and governments claiming that nuclear energy is safe, the accident in 1986 came totally unexpected. No one had a plan. For 17 days the cloud of radioactive contamination traveled around the globe and taught the world a lesson: There is no place safe.
Verzio Film Festival Submission
Keywords: Documentary films